Analysis of Understanding of Sharia Financial Literacy and Trust in the Use of Sharia Fintech among Employees of the El Fajr Quran House Education Foundation, Palembang - Bagus Setiawan; Ria Astina; Cindi Pramita (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the understanding of Islamic financial literacy and trust in the use of Islamic fintech among employees of the El Fajr Quran House Education Foundation in Palembang. The study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation of purposively selected employees. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results show that most employees understand the basic concepts of Islamic financial literacy, particularly regarding the prohibition of usury (riba), gharar (gharar), and maysir (gambling). However, understanding of Islamic fintech products and services remains diverse. Trust in the use of Islamic fintech is influenced by compliance with Islamic principles, system security, ease of use, information transparency, and the legality of the provider. Good Islamic financial literacy also increases employee confidence in utilizing Islamic fintech services. Therefore, increased education and outreach regarding Islamic fintech are needed to improve user understanding and trust, thereby supporting financial activities in accordance with Islamic economic principles.